O profissional de Letras atuante em aulas privadas de Inglês: o conceito de teacherpreneur e as competências necessárias para um fazer pedagógico transformador - Soster, Juliana Teixeira (Universidade do Vale do Rio dos Sinos, 2021)
This study aims to understand and reflect on the skills needed by a Letras professional who works in the segment of private classes of additional languages, specifically, English. To determine the objective of this work, I present concepts related to teaching an additional language which, in the scope of this research, is focused on teaching English, and the definition of the entrepreneurial teacher today, as well as their role in the digital world (Lafford and Ramírez (2018), Gómez (2016), Berry, Byrd, Wiede, (2013), Schlatter and Garcez (2009), Crystal (2003), Nóbrega (2016). In order to verify how undergraduates and graduates in Letras who work in this environment perceive their professional practices and what skills and competences they consider necessary for a Letras professional who works or wants to work in the segment of private additional language classes, six entrepreneurial teachers and two students from private English classes were interviewed using semi structured questionnaires. The results show that an entrepreneurial teacher who wants to act autonomously in the field of private English classes needs to acquire many skills that interact with each other, such as linguistic skills, management and digital skills, and also to be able to correlate all the necessary skills to manage their classes and their business.
Keywords: Ensino/aprendizagem de inglês como LA; Professor empreendedor; Teacherpreneur; Ensino de Inglês em contexto de aulas privadas; Língua adicional; Teaching/learning English as an AL; Entrepreneurial teacher; Teaching English in the context of private lessons; Additional language